A CLINICAL STUDY TO STANDARDIZE THE PROCEDURE OF DHANYAMLA DHARA AND TO ASSESS ITS EFFICACY IN RHEUMATOID ARTHRITIS - Arun Kumar Bhadula; K. Ravisankaran; S. Seena; Parul Singh; Sarada Ota (International Journal of Ayurveda and Pharma Research, 2015)
In this era of globalization and standardization there is a dire need to arrive at a consensus in the approach to the treatment of the diseases in Ayurveda. It is an essential tool not only for proper understanding of the pathology, appropriate diagnosis, and treatment, but also for scientific documentation and generation evidence for global acceptance and appreciation among the scientific community.Classics clearly demarcate the effects of Sweda as an operative and as a pre-operative/post-operative (or both procedures). Considering the therapeutic importance of one such Swedana modality, study was attempted on standardization of the procedure of Dhanyamla dhara, a form of Parisheka sweda.Based on the references in the classics, the data collected through questionnaires and personal interviews a protocol was developed and it was clinically tested in the disease, Rheumatoid Arthritis. The study was carried out in the Department of Panchakarma, Government Ayurveda College, Tripunithura. Patients diagnosed of Rheumatoid Arthritis (As per American College of Rheumatology revised criteria 1987) under the age group of 16-60 years were selected according to the inclusion criteria and were admitted to the IP Unit. Assessment was done by using clinical parameters (objective and subjective) before treatment and after treatment. The results were statistically analyzed using the most appropriate statistical tests. Significant results were noted in all the clinical parameters such as joint pain, joint swelling, tenderness, general functional capacity signifying the effectiveness of Dhanyamla dhara in improving the clinical features and quality of patients life.